Hybridization of Energy Efficient Clustering and Multi-Heuristic Strategies to Increase Lifetime of Network - Kohli, Dazy; Deepak, (International Journal of Computer Sciences and Engineering, 2020)
Conserving energy so that data collection can be prolonged is discussed through this paper. Lack of time and hectic life causes disease to spread at wild rates. To this end, technology plays critical role in the detection and prevention of diseases. IoT(internet of things) is an emerging field that operates on real time datasets to detect any abnormality through classification modeling. Sensor is an integrated component of IoT that is used to collect data and then store within data store. Sensors have limited energy associated with them. There are number of mechanisms including LEACH, DEEC, MDEEC, EDEEC etc. all these mechanisms conserve energy but optimization in each protocol is missing. Problems associated with listed protocols are discussed and mechanisms used to overcome the problems are also briefed. Comparative analysis suggests DEEC protocol is best among all and can be used for optimization purpose. Health predictions will be better in case sensors are in good health.